A platform for a dialogue to be continued. Forward thinking in agriculture and food - Hubert, Bernard; Brossier, Jacques; Caron, Patrick; Fabre, Pierre; de Haen, Hartwig; Labbouz, Benoît; Petit, Michel; Treyer, Sébastien (Perspective, 2010)
<span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value=""1":2,"2":"How can agriculture produce food for 9 billion inhabitants in 2050 and achieve the Millennium Development Goals of alleviating poverty, reducing hunger and protecting the environment? In order to take up these challenges and to design tomorrow’s food and agriculture systems, research organizations have to define strategies and options, and public policy makers their priorities from now on, relying on foresight studies. Various studies have been conducted to assess scenarios for the long-term future of food and agriculture in the world. Each one has its own objectives, methodologies, and results. Analyzing, comparing and discussing hypotheses, methodologies and results were the objectives of the FI4IAR/CTA seminar “Thinking Forward: assessments, projections and foresights”, organized during the GCARD 2010 process. This dialogue, which sometimes led to scientific disputes, proved productive"" data-sheets-userformat=""2":589,"3":[null,0],"5":"1":["1":2,"2":0,"5":[null,2,0],"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"6":"1":["1":2,"2":0,"5":[null,2,0],"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"9":0,"12":0">How can agriculture produce food for 9 billion inhabitants in 2050 and achieve the Millennium Development Goals of alleviating poverty, reducing hunger and protecting the environment? In order to take up these challenges and to design tomorrow’s food and agriculture systems, research organizations have to define strategies and options, and public policy makers their priorities from now on, relying on foresight studies. Various studies have been conducted to assess scenarios for the long-term future of food and agriculture in the world. Each one has its own objectives, methodologies, and results. Analyzing, comparing and discussing hypotheses, methodologies and results were the objectives of the FI4IAR/CTA seminar “Thinking Forward: assessments, projections and foresights”, organized during the GCARD 2010 process. This dialogue, which sometimes led to scientific disputes, proved productive